Opinion survey on green laboratory management in Thailand among chemical laboratory workers - Kreunin, Paweena; Paibulpanich, Akarin; Yeadyad, Laddawan; Chaosrimud, Duangkamol; Kantanyarat, Anantanat (Bulletin of Applied Sciences, 2022)
This survey research, using questionnaire, investigates the opinion of personnel working in the chemical-based laboratories regarding green laboratory management in Thailand. The main objectives are to study their basic knowledge and understanding of green laboratory concepts, and their suggestions on the development of green laboratory management. 4,800 questionnaires were distributed to the training participants of the Department of Science Service, Ministry of Higher Education, Science, Research and Innovation, both by mails and at the training service sites. 2,112 questionnaires were returned and indicated as laboratory workers who used chemicals, which, in turn, constitutes our sample. We found that most of the respondents had a basic knowledge and understanding of the safety and sustainability principles of the green laboratories, by means of efficient use of resources and being environmentally friendly. They understood the importance of green laboratory management, and expressed the need of its development in Thailand. Moreover, the majority of respondents suggested that the development entails the administrative sections from both government and organizations to provide clear policy, and guidelines, as well as knowledge, and actively campaign to raise awareness, knowledge and understanding of those involved. The future study is the impact of such operation implemented. The information acquired will be an integral part that enhances laboratory qualities to drive the manufacturing and service sectors of Thailand substantially.